Rehabilitation and the retarded offender - Browning, Philip L. (Springfield Charles C Thomas, 1976)
This volume brings together a body of knowledge on the much neglected topic of what is referred to as the naive or retarded offender. The unique complexities assocated with the rehabilitation of either mentally retarded persons or public offenders alone are immense in and of themselves.
Keywords: Law